Sodium-Calcium Exchangers in Rat Trigeminal Ganglion Neurons. (29th April 2013) - Kuroda, Hidetaka; Sobhan, Ubaidus; Sato, Masaki; Tsumura, Maki; Ichinohe, Tatsuya; Tazaki, Masakazu; Shibukawa, Yoshiyuki
Background: Noxious stimulation and nerve injury induce an increase in intracellular Ca 2+ concentration ([Ca 2+ ]i) via various receptors or ionic channels. While an increase in [Ca 2+ ]i excites neurons, [Ca 2+ ]i overload elicits cytotoxicity, resulting in cell death. Intracellular Ca 2+ is essential for many signal transduction mechanisms, and its level is precisely regulated by the Ca 2+ extrusion system in the plasma membrane, which includes the Na + -Ca 2+ exchanger (NCX). It has been demonstrated that Ca 2+ -ATPase is the primary mechanism for removing [Ca 2+ ]i following excitatory activity in trigeminal ganglion (TG) neurons; however, the role of NCXs in this process has yet to be clarified. The goal of this study was to examine the expression/localization of NCXs in TG neurons and to evaluate their functional properties. Results: NCX isoforms (NCX1, NCX2, and NCX3) were expressed in primary cultured rat TG neurons. All the NCX isoforms were also expressed in A-, peptidergic C-, and non-peptidergic C-neurons, and located not only in the somata, dendrites, axons and perinuclear region, but also in axons innervating the dental pulp. Reverse NCX activity was clearly observed in TG neurons. The inactivation kinetics of voltage-dependent Na + channels were prolonged by NCX inhibitors when [Ca 2+ ]i in TG neurons was elevated beyond physiological levels. Conclusions: Our results suggest that NCXs in TG neurons play an important role in regulating Ca 2+ -homeostasis and somatosensory information processing by functionally coupling with voltage-dependent Na + channels.